Visible‐Light‐Driven Selective Air‐Oxygenation of C−H Bond via CeCl3 Catalysis in Water. Issue 13 (2nd May 2021) - Xie, Pan; Xue, Cheng; Shi, Sanshan; Du, Dongdong
Abstract: Visible‐light‐induced C−H aerobic oxidation is an important chemical transformation that can be applied for the synthesis of aromatic ketones. High‐cost catalysts and toxic solvents were generally needed in the present methodologies. Here, an efficient aqueous C−H aerobic oxidation protocol was reported. Through CeCl3 ‐mediated photocatalysis, a series of aromatic ketones were produced in moderate to excellent yields. With air as the oxidant, this reaction could be performed under mild conditions in water and demonstrated high activity and functional group tolerance. This method is economical, highly efficient, and environmentally friendly, and it will provide inspiration for the development of aqueous photochemical synthesis reactions. Abstract : Mild conditions : A mild and efficient aqueous photocatalytic strategy is established for the synthesis of aromatic ketones via CeCl3 ‐catalyzed selective air‐oxygenation of C−H bonds. With air as the oxidant and water as the solvent, this methodology demonstrates good economy, high efficiency, and environmental friendliness.